(untitled) (Washington, D.C., 1999)
The book contains primary readings and documents from the ereas of literature, politics, the arts, intellectual and social thought, and popular culture. The readings in each volume have been selected to provide an overview of the evolution of American culture are intended to reflect the complexity and diversity of the American experience.
Keywords: American literature,United States; Civilization,Sources; 20th century,20th century